Leader-Member Exchange (LMX) within team contexts: a look beyond the leader-member dyad - Furtado, Liliane Magalhães Girardin Pimentel (2016)
Leader–member exchange (LMX) theory focuses on the quality of the member’s exchange relationship with the leader. A fundamental tenet of LMX theory is that leaders develop different quality relationships with members in their teams. Research on LMX has almost exclusively focuses on LMX relationships as independent dyads within work groups. However, LMX relationship cannot be fully understood in isolation from the team contexts that shape it. As a result, LMX research has been criticized for failing to consider the role of the social context in the development of members’ perceptions of LMX. This deficiency prompted researchers to call for more research on LMX within the context of teams. Thus, this dissertation answer this call by considering LMX within the team context by exploring theoretical approaches that take into account the social context in which LMX is embedded. Drawing on LMX theory, social comparison theory and social network approach, I address this question through two empirical and independent papers aimed to consider LMX as systems of interdependent dyadic relationships, rather than independent dyads. Overall, the findings of this dissertation corroborate prior arguments that LMX theory represents not only a dyadic phenomenon, but also captures a complex multilevel phenomenon beyond the dyadic relationship. The contributions of these findings are discussed.